2022
DOI: 10.1002/marc.202200120
|View full text |Cite
|
Sign up to set email alerts
|

Donor–Acceptor Stenhouse Adduct‐Polydimethylsiloxane‐Conjugates for Enhanced Photoswitching in Bulk Polymers

Abstract: Donor-acceptor Stenhouse adducts (DASAs) are a rapidly emerging class of visible light-activated photochromes and DASA-functionalized polymers hold great promise as biocompatible photoresponsive materials. However, the photoswitching performance of DASAs in solid polymer matrices is often low, particularly in materials below their glass transition temperature. To overcome this limitation, DASAs are conjugated to polydimethylsiloxanes which have a glass transition temperature far below room temperature and whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…7). 32 Analogous experiments performed using indoline and diethylamine produced similar results (Supplementary Figs. 8 and 9).…”
Section: Mechanically Gated Dasa Formation In Polymeric Materialssupporting
confidence: 55%
“…7). 32 Analogous experiments performed using indoline and diethylamine produced similar results (Supplementary Figs. 8 and 9).…”
Section: Mechanically Gated Dasa Formation In Polymeric Materialssupporting
confidence: 55%
“…41,47 When held at or above the host polymer's T g , DASA switching kinetics markedly improve. 38,41,46 Studies by Sroda et al . have also shown that the level of DASA functionalisation itself affects T g and elastic modulus of the host polymer, 38 while Yap et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the solid state, effective and reversible switching of polymer-bound DASAs is dependent on the polymer's glass transition temperature (T g ) 41,47 . When held at or above the host polymer's T g , DASA switching kinetics markedly improve 38,41,46 . Studies by Sroda et al have also shown that the level of DASA functionalisation itself affects T g and elastic modulus of the host polymer 38 , while Yap et al demonstrated polymer chain-length dependence on DASA switching performance, with shorter chains of (~20 monomer units) showing faster switching compared to longer chain-lengths of (~100 monomer units) 43 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations